Analisis Strategi dan Karakteristik Perusahaan terhadap Kualitas Laba - Idhastari, Suwindha (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2021)
This study aims to determine the effect of company strategy proxied byÂ cost leadership strategy, differentiation strategy and investment opportunity set, and company characteristics proxied by company size, managerial ownership structure, institutional ownership structure and audit quality on earnings quality in manufacturing companies listed on the Indonesia Stock Exchange 2015-2019. The population in this study were 175 companies with a total sample size 37 compenies. The method used in determining the number of samples in purposive sampling. Regression analysis in this study using multiple linier regression. The result of this study indicate that the cost leadership strategy, investment opportunity set, managerial ownership structure, and institutional ownership structure have no effect on earnings quality. Meanwhie, the differentiation strategy, company size and audit quality have an effect on earnings quality. The result of multiple liniear regression analysis showed an adjusted R2 value of 0,342. This shows that the level of reletionship between the variable cost leadership strategy, differentiation strategy, investement opportunity set, company size, managerial ownership, institutional ownership, and audit quality on earnings quality is 34,2% and the remaining 65,8% is explained by other variables in beyond the research model.